2023
DOI: 10.3390/cancers15051524
|View full text |Cite
|
Sign up to set email alerts
|

The Tissue Factor Pathway in Cancer: Overview and Role of Heparan Sulfate Proteoglycans

Abstract: Historically, the only focus on tissue factor (TF) in clinical pathophysiology has been on its function as the initiation of the extrinsic coagulation cascade. This obsolete vessel-wall TF dogma is now being challenged by the findings that TF circulates throughout the body as a soluble form, a cell-associated protein, and a binding microparticle. Furthermore, it has been observed that TF is expressed by various cell types, including T-lymphocytes and platelets, and that certain pathological situations, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 347 publications
0
10
0
Order By: Relevance
“…Beyond cancer-induced hypercoagulability, dysregulation of TF-associated signalling pathways and their constituents play an important role in tumour progression, particularly by impacting angiogenesis and tumour invasion. While TF shows tumour-enhancing characteristics, its natural inhibitors, TFPI1 and TFPI2, are associated with tumour-suppressing properties [154].…”
Section: Tfpi2as1mentioning
confidence: 99%
“…Beyond cancer-induced hypercoagulability, dysregulation of TF-associated signalling pathways and their constituents play an important role in tumour progression, particularly by impacting angiogenesis and tumour invasion. While TF shows tumour-enhancing characteristics, its natural inhibitors, TFPI1 and TFPI2, are associated with tumour-suppressing properties [154].…”
Section: Tfpi2as1mentioning
confidence: 99%
“…These findings are relevant given the importance of coagulation disorders in breast cancer patients. Additionally, this study revealed that the removal of HS chains from the SDC3 did not promote the release of TFPI in these cells, suggesting that SDC3-TFPI binding is not dependent on HS attached to SDC3 [ 43 , 44 ]. In another work, Wu and collaborators failed to show a correlation between SDC3 expression in breast carcinoma and lymph node metastasis [ 45 ].…”
Section: Syndecans’ Expression In Breast Cancer Cell Lines and Its Co...mentioning
confidence: 99%
“…Several excellent reviews on extracellular and cell surface HS–PGs exist in the literature. The interested reader is referred to these for further information [ 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 ]. In this review, the more important aspects of HS interactive components with representative examples of HS–PGs, such as perlecan and the syndecan, will be covered.…”
Section: Hs Interactive Proteinsmentioning
confidence: 99%